WHOSE AUTONOMY SHOULD BE RESPECTED IN ART? - DELVIGNE, Annick (MEDECINE LEGALE DROIT MEDICAL, 2025)
Assisted Reproductive Technology (ART) is a discipline originally developed to address the biological difficulties encountered in a parental project within a heterosexual couple. These techniques which separate sexual intercourse from conception and allow for the freezing of gametes (eggs and sperm) and embryos has opened up possibilities and creative options for procreation. This situation leads to the question of the autonomy of participants: Does the caregiver have the autonomy to refuse a reproductive project? If so, what criteria will be used to refuse it, and to what extent does this challenge the patient’s autonomy to access his or her legal project? Does the patient have the autonomy to carry out his or her project, if it is technically and legally feasible? If this is the case, does the caregiver, who is obliged to make his or her expertise available for the patient’s decision, manage to ensure that the patient’s autonomy is respected despite the instrumentalization of his or her practices? The challenging decision-making exercise is to find a balance between these two legitimate autonomies, knowing that the autonomy of some will often restrict that of others and will revolve around the well-being of a third party who does not yet have a say but whose future is at stake. This balancing act is the daily life of ART centers that have not taken the path of arbitrariness, which we will try to develop in this article.